IMMUNOBIOCHEMICAL MARKERS OF CARDIAC REVASCULARISATION DURING AORTOCORONARY BYPASS SURGERY IN PATIENTS WITH CORONARY HEART DISEASE UNDER ARTIFICIAL CIRCULATION (World Bulletin of Public Health, 2024)
Coronary heart disease (CHD) is one of the leading causes of mortality worldwide, and aortocoronary bypass surgery (ACS) continues to be the gold standard for the treatment of patients with CHD. ACH surgery can be performed with or without the use of artificial circulation. A number of studies have shown that ACS operation, mainly in the mode of artificial circulation, leads to changes in cellular immunity in the preoperative and early postoperative period. The mechanisms of immune response regulation in patients during and early after surgical revascularisation are not fully understood. Previous studies have emphasised the fundamental role of cytokines and chemokines in coronary atherogenesis, atherosclerotic plaque formation, cardiovascular inflammatory changes, acute coronary thrombosis and CHD. The aim of this review is to study the currently available significant immunobiochemical markers of prognosis of complications during aortocoronary bypass surgery under artificial circulation, as well as various immune mechanisms involved in the pathogenesis of CHD in patients undergoing ACS.